2007
DOI: 10.1017/s1360674307002341
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in the function and frequency of Standard English genitive constructions: a multivariate analysis of tagged corpora

Abstract: This study of present-day English genitive variation is based on all interchangeable instances of s-and of-genitives from the 'Reportage' and 'Editorial' categories of the 'Brown family' of corpora. Variation is studied by tapping into a number of independent variables, such as precedence of either construction in the text, length of the possessor and possessum phrases, phonological constraints, discourse flow, and animacy of the possessor. In addition to distributional analyses, we use logistic regression to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
195
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(208 citation statements)
references
References 49 publications
9
195
1
3
Order By: Relevance
“…that long possessums favor s-genitive usage in AmE but not in BrE; see Hinrichs & Szmrecsanyi 2007). The reason for this, then, may well be that spoken vernaculars of the type covered in our datasets are more homogeneous than written varieties.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 85%
See 4 more Smart Citations
“…that long possessums favor s-genitive usage in AmE but not in BrE; see Hinrichs & Szmrecsanyi 2007). The reason for this, then, may well be that spoken vernaculars of the type covered in our datasets are more homogeneous than written varieties.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 85%
“…We will not speculate as to why our results are different from Hundt and Szmrecsanyi (2012) except to note that their study examined data of a different time period (late 19th and early 20th century) and medium (written) from ours. Next, we saw earlier that previous studies comparing AmE to BrE have reported a number of probabilistic contrasts, such as inanimate possessors discouraging s-genitive usage less strongly in AmE than in BrE, and/or animate possessor more strongly favoring the s-genitive in BrE than in AmE (Jahr Sohrheim 1980; Hinrichs & Szmrecsanyi 2007;Szmrecsanyi & Hinrichs 2008;Szmrecsanyi et al 2014). The previous literature also suggests that in the written medium at least, long possessums favor s-genitive usage in AmE but not in BrE (Hinrichs & Szmrecsanyi 2007).…”
Section: Genitive Variation: Interim Summarymentioning
confidence: 79%
See 3 more Smart Citations